THE EFFECT OF INFORMATION SYSTEM ON ACHIEVEMENT OF CONSTRUCTION PROJECT IN JABODETABEK REGION - Agus Suroso; Endang Siti Astuti; Hamidah Nayati Utami; Zainal Arifin (Universitas Mercu Buana, 2020)
The contribution of information systems on Project success become an interesting topic to investigate, especially in a construction project. The project successfully achieved when the information system was well used with appropriate communication knowledge in a construction project. However, in worker perspectives, the role of the information system in a construction project is not significant to achieve the project's success due to it indicated by the main indicator which is the finish on schedule, high quality and within budget. Therefore, this research aims to investigate the correlation and effect between IS to project success in terms of product quality and on-time finish the project. This research was conducted through a questionnaire and survey analysis. The total respondent is 105 that consists of 23 Project Manager (PM), 13 Vice PM and 69 site coordination. The data was analyzed by SPSS and Smart PLS software. The result shows that there is a significant effect of system quality to Information quality with CR value of 5.174, system quality to project success has CR value of 3.564 and information quality to project success has CR value of 2.037. It can be concluded that IS was very important to ensure the project success especially in a construction project in Jabodetabek Region.